2020
DOI: 10.1021/acs.jmedchem.0c00245
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Potent, Selective, and Orally Bioavailable Inhibitors of USP7 with In Vivo Antitumor Activity

Abstract: USP7 is a promising target for cancer therapy as its inhibition is expected to decrease function of oncogenes, increase tumor suppressor function, and enhance immune function. Using a structure-based drug design strategy, a new class of reversible USP7 inhibitors has been identified that is highly potent in biochemical and cellular assays and extremely selective for USP7 over other deubiquitinases. The succinimide was identified as a key potency-driving motif, forming two strong hydrogen bonds to the allosteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 24 publications
3
36
0
Order By: Relevance
“…Moreover, extensive retrospective work has established that these water site free energies correlate with experimentally measured binding free energies for both small molecules [ 18 , 27 , 28 ] and peptides [ 25 ], as was predicted from theory [ 23 ], although in practice prediction of free energies is now performed using free-energy perturbation [ 29 , 30 ]. Nonetheless, prospective studies from drug discovery programs have since demonstrated that displacement or replacement of a water molecule from an unstable site will reliably contribute favorably to binding, and thus these water sites can serve to guide the placement of functional groups for optimizing potency [ 31 , 32 ]. As a result, interpreting peptide toxin interactions with ion channels in terms of the water sites they displace or replace upon binding might present a new framework for understanding peptide toxin potency and SAR.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, extensive retrospective work has established that these water site free energies correlate with experimentally measured binding free energies for both small molecules [ 18 , 27 , 28 ] and peptides [ 25 ], as was predicted from theory [ 23 ], although in practice prediction of free energies is now performed using free-energy perturbation [ 29 , 30 ]. Nonetheless, prospective studies from drug discovery programs have since demonstrated that displacement or replacement of a water molecule from an unstable site will reliably contribute favorably to binding, and thus these water sites can serve to guide the placement of functional groups for optimizing potency [ 31 , 32 ]. As a result, interpreting peptide toxin interactions with ion channels in terms of the water sites they displace or replace upon binding might present a new framework for understanding peptide toxin potency and SAR.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, compound 41 is a reversible, highly potent, selective, and orally bioavailable USP7 inhibitor. In in vivo xenograft models of multiple myeloma, this molecule impairs the tumor growth of both p53 wild-type and mutant tumor cell lines, confirming that USP7 inhibition can suppress tumor growth affecting different pathways [171].…”
Section: Hh-related Dubs: Inhibitors and Therapeutic Applicationsmentioning
confidence: 74%
“…[195][196][197][198] IP: intraperitoneal; IV: intravenous; SC: subcutaneous. C19 [167] Spongiacidin C [169] XL177A [170] Compound 41 [171] [171]…”
Section: Hh-related Dubs: Inhibitors and Therapeutic Applicationsmentioning
confidence: 99%
“…A number of SBDD studies have successfully used Schrodinger suite of applications for drug designing, drug repurposing, understanding drug interaction at receptor site, and property analysis 22,23 . Models for selective lipoxygenase inhibitors, design principles for non‐nucleoside inhibitors for HIV‐1 reverse transcriptase (NNRTIs), design, and validation of tumor growth inhibitors are few examples of the wide range of application of SBDD using Schrodinger suite of applications 24–27 …”
Section: Introductionmentioning
confidence: 99%
“…22,23 Models for selective lipoxygenase inhibitors, design principles for non-nucleoside inhibitors for HIV-1 reverse transcriptase (NNRTIs), design, and validation of tumor growth inhibitors are few examples of the wide range of application of SBDD using Schrodinger suite of applications. [24][25][26][27] The present study evaluates the action of the commonly used drugs for treating OLP at HSP70 and TNFα using molecular docking. Through this study, we attempt to understand the interaction of drug at target site and discuss the clinical utility and future possibility of such studies.…”
mentioning
confidence: 99%